Dermatoglyphic findings in dental caries: a preliminary report - (:unkn) unknown (My University, 1998)
The dermatoglyphs of caries-free students and the students with dental caries in 10 or more teeth were compared. The caries-free students had an increased frequency of ulnar loops on all fingers. In contrast, the students with dental caries had an increased frequency of whorls on all fingers.
Keywords: Female; Humans; Male; Dental Caries; Dental Caries Susceptibility; Dermatoglyphics